TINGKAT DAYA TETAS TELUR UDANG GALAH (Macrobranciun rosenbergii) DENGAN SALINITAS YANG BERBEDA - Anny Rimalia; Elrifadah Elrifadah; Jumansyah Jumansyah (Universitas Lambung Mangkurat, 2017)
The aim of this study was to obtain the best salinity for honey prawn (macro) egg prawn (Macrobrancium rosenbergii). This study used Completely Randomized Design, with three treatments and three replications. The results showed that with the salinity of 6 ‰ resulted in an average hatchability of 86.4%, with the salinity of 8 ‰ resulted in 70.5% hatchability, and at salinity 10 ‰ yielded hatchability of 56, 5%. The result of analysis of variance (ANOVA), hatching power of prawn egg very different between treatment. Water quality such as temperature, DO, and pH, during the study can still be tolerated by giant prawns. The results of this study recommend using a salinity of 6 ‰ to do hatching of prawn eggs.